Reintegrating older long-term unemployed workers: The impact of temporary job guarantees - Alexander Ahammer; Martin Halla; Pia Heckl; Rudolf Winter-Ebmer (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2026)
Long-term unemployment among older workers is particularly difficult to overcome. We study the impacts of a large-scale job guarantee program that offered up to two years of fully subsidized employment to long-term unemployed individuals aged 50 and above. Using a sharp age-based discontinuity in eligibility, we find that participation increased regular, unsubsidized employment by 43 percentage points two years after the program ended. The gains are driven by transitions into new firms and industries, rather than continued subsidized employment, and we find no evidence of displacement effects for non-participants or spillovers to family members. The program had no measurable short-run health effects.
Keywords: J64; J08; J78; I14; H51; 330; Long-term unemployment; temporary job guarantee; subsidized employment; health status